Hubungan Pendidikan, Pekerjaan Ibu dan Riwayat Pemberian ASI Dengan Kejadian Stunting Pada Anak Sekolah Dasar - Septi Maynarti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Stunting is a nutritional problem in both poor and developing countries. Many factors cause stunting, including education, maternal occupation, and the history of breastfeeding. The purpose of this study was to determine the relationship between education, maternal occupation, the history of breastfeeding, and theincidence of stunting in elementary school students. This study used a cross sectional design.The population in this study was elementary school students in the Tuah Negeri Sub-district, Musi Rawas Regency, and the sample used was 97 students. The sampling technique used a cluster sampling technique. Data collection used questionnaire and measurement of height directly based on the index height/age. This study also examined the characteristics of the mother, namelymother’s education and occupation. Data analysis used chisquare test. The research was conductedatthe Elementary School of Tuah Negeri Sub-district, Musi Rawas Regency in June 2020. Theresults showed the proportion of stunted children was 30.9%, where most of the pupils had normal height (not stunting), namely 69.1%. The results of the bivariate analysis showed that the variable associated with the incidence of stunting in elementary school children was the history of breastfeeding(p-value=0.000).Meanwhile, theunrelated variables were maternal education (P-value = 0.645) and maternal occupation (p-value = 0.111). According to the results of the study, it is suggested that a more intensive personal approach is needed as preventive and promotive efforts to change behavior or parenting style in improving nutritional status by introducing good behavior the mothers of students with normal height and spreading these good behaviors to mothers of stunting children and otherparents.